2006
DOI: 10.1158/1535-7163.mct-05-0339
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of androgen-independent prostate cancer using a prostate restricted replicative adenovirus and a replication-defective adenovirus encoding human endostatin-angiostatin fusion gene

Abstract: Although prostate-restricted replicative adenovirus has exhibited significant antitumor efficacy in preclinical studies, it is necessary to develop more potent adenoviruses for prostate cancer gene therapy. We evaluated the synergistic killing effect of prostate-restricted replicative adenovirus and AdEndoAngio, a replication-defective adenovirus expressing the endostatin-angiostatin fusion protein (EndoAngio). When coadministered with AdEndoAngio, prostate-restricted replicative adenovirus significantly eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The efficacy of combination therapy with conventional gene therapy using replication-deficient adenovirus plus virotherapy has been reported previously (27,28). Combined with tumor-specific replication-selective adenovirus, replication-deficient adenoviruses were able to replicate and spread to surrounding tumor cells.…”
Section: Discussionmentioning
confidence: 80%
“…The efficacy of combination therapy with conventional gene therapy using replication-deficient adenovirus plus virotherapy has been reported previously (27,28). Combined with tumor-specific replication-selective adenovirus, replication-deficient adenoviruses were able to replicate and spread to surrounding tumor cells.…”
Section: Discussionmentioning
confidence: 80%
“…A confluent monolayer of HUVEC cells was scratched, displaced cells were removed, and fresh medium containing CM was added. The gap distances were quantified (12), and data are presented as a comparison value (the gap distance at 12 h/initial distance). ++, P < 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…In our past studies, we developed a prostate-restricted replicative adenovirus (PRRA; ref. 14) and investigated the synergistic antitumor effect of PRRA combined with a replication-defective adenovirus encoding an endostatin and angiostatin fusion gene (EndoAngio) in androgen-independent prostate cancer (12). We observed that PRRA augmented the transduction effect and expression of antiangiogenic factor, showing a significant antiangiogenic and antitumor effect.…”
mentioning
confidence: 99%
“…[4][5][6] The existing therapy for metastasis of PCA is unsatisfactory, with the condition being invariably fatal. [6][7][8] The development of novel therapies, possibly including gene therapy, for management of PCA is thus a clinical priority.…”
Section: Introductionmentioning
confidence: 99%